Evaluación varios fungicidas y un entomopatogeno para el control de sigatoka negra mycosphaerella fijiensis en banano orgánico - Alcívar Campoverde, Bernardo Simón (2014)
At Hacienda Andreina, located on the premises San Luis Province of Cañar Region The Trunk, Cañar Province, eastern banana zone 4, the investigation was developed to quantify the effectiveness of fungicides to control black Sigatoka organic bananas. The objectives were; Assess the level of incidence and control of black Sigatoka studied. Analyze meet the varying treatments; Emission rate of leaf and plant height at the beginning and end of the trial, pseudo stem diameter According to the classification of Holdridge the zone corresponds to rainforest (BHT ) ; the annual precipitation: 1650 mm , average temperature 26 ° C maximum 32.0 ° C and 19.7 ° C minimum . The test was performed on a template banana Williams. Fungicide treatments were: Biorgan, Blindax, Trichoderma harzianum, Sonata, Timorex, Plandak, Sting, Custon bio, Desfan and Python. The experimental unit was one leaf per plant, distributed in a randomized block with four replications The total volume per hectare was 18.92L. Banana plants began to prepare when children had a height of 1.25 to 1.40 m. Fertilization was done manually, only be performed once with Fertil and Potassium sulphate . Watering it was not carried out because this test was run during the rainy season. Statistical analysis of infection rates and percentage of burning leaf samples yielded no statistically significant according to the corresponding analysis of variance context in which rates of progress of infection fungus black Sigatoka were adjusted a statistical model that interrelate time in weeks with infection rates in all the investigated organic fungicides . Increased rates of infection was lower with 2.30 % per week for Phyton (Cu sulfate) fungicide with an index of determination 0.94. The highest rates of infection was increased to Biorgan fungicides (Bacillus subtilis), Trichoderma harzianum, Sting (Bacillus subtilis) and Bio Custon 5 with 4.24 to 5.62 % / week. Burning in the leaf was highly variable monitored producing high coefficients of variation between 27.76 % to 9.27% at the end of the evaluation. Rates of disease progression and the percentage of leaf area burned monitored highly correlated 100% accuracy (R2 = 1.0), and none of the fungicides were efficient when burning exceeded 80 %. Regarding the other variables treatments did not differ from absolute control.